Korelasi Agama, Filsafat dan Ilmu - Abd Wahid (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2012)
Seeking the truth is one of that a man does in his life. Standard of the truth  is dependent on media, which is employed by the man. There are there media,  which are used by a man in seeking the truth. They are; religion, philosophy, and  knowledge or science. Truth provided by religion tends to rely on truth-values that  are referred to God. The truth produced by philosophy tends to provide deep  reflective thought, which are less connected to God. While the truth afforded by  science consists of knowledge values that are inconsistent and changeable  following the human life development.